Maladaptive behavior in people with intellectual disabilities - Bojana Mastilo; Sladjana Ćalasan (Биомедицинска истраживања, 2020)
The aim of the study is to provide better understanding of the prevalence and forms of maladaptive behavior, as well as of the factors associated with this behavior in people with intellectual disability, by Reviewsing the available literature. Maladaptive behavior is behavior that is common enough and/or severe enough to limit a person's ability to function properly in everyday life, learn new skills, and gain access to social resources. It covers a whole range of behaviors such as: physical aggression towards things or people, self-harm, stereotypical behavior, sexually inappropriate behavior, abusive behavior, etc. Studies highlight considerable variations in the prevalence of maladaptive behavior in individuals with IO ranging from 5.7% to 63.9%. The appearance of maladaptive behavior can be influenced by several factors, the most significant of which are the following: gender, age, severity of IO, additional impairments, residential environment, cognitive-emotional factors, communication dysfunction, etc. A common feature of all these behaviors is the negative effect on the quality of life of the person and the staff caring for them. In addition to psychotropic drugs and behavioral methods, various psychotherapy methods, cognitive and emotional training, creative therapeutic methods and functional behavior analysis are used in the treatment of maladaptive behavior. The condition is that they are tailored to the individual's developmental level and his or her way of communication.
Keywords: maladaptive behavior; intellectual disability; prevalence; risk factors